Carcinoma mamário sólido em porquinho da índia (Cavia porcellus): relato de caso - Dias, Marília Marinho Banhos (Universidade Federal Rural do Semi-Árido, 2021)
The increasing number of cases of guinea pigs (C. porcellus) as pets in the wild animal clinic brings the importance of further studies on this species. The increase of neoplasms in the clinic is directly related to the increase in life expectancy. Thus, the present study aims to describe a solid carcinoma in a guinea pig. Mammary neoplasms are common, and, among them, the solid carcinoma is reported with a certain frequency in mammalian clinics, having an invasive and undifferentiated characteristic, which enables the occurrence of metastasis development. The animal was taken to the Veterinary Hospital of the Universidade Federal Rural do Semiárido, in the wild animal sector. In the anamnesis it was reported that the animal had been adopted two months ago and already presented a nodule in the left mammary gland, which released a serosanguinolent content and showed pain when palpated. In the clinical examination the animal presented usual behavior, and on palpation of the nodule it was possible to notice that the animal felt pain and that even without being palpated, the gland was releasing a bloody liquid. To obtain the diagnosis a cytology exam and ultrasonographic exam were performed, which did not provide a conclusive result, therefore it was necessary to perform a histopathological examination. The histopathological evaluation showed multilobulated and non-encapsulated neoplastic cell proliferation, expanded throughout the subcutaneous and dermis. The cells presented pleomorphism, anisocytosis, anisokaryosis and atypical mitoses, these being characteristics of malignant neoplasms, and the final diagnosis was solid cell carcinoma. After the procedure of simple mastectomy and post-surgical treatment the patient was completely recovered.
Keywords: Neoplasia mamária; Roedores; Clínica Médica e Cirúrgica de Animais Silvestres; Oncologia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA